ChemInform Abstract: Unique Features of Chiral Palladium Enolates Derived from β‐Ketoamide: Structure and Catalytic Asymmetric Michael and Fluorination Reactions. Issue 50 (December 2015) - Hayamizu, Kenji; Terayama, Naoki; Hashizume, Daisuke; Dodo, Kosuke; Sodeoka, Mikiko
Abstract: Chiral Pd‐BINAP complexes catalyze enantioselective Michael and fluorination reactions of β‐ketoamides and β‐ketoesters in which Pd‐enolate intermediates play a key role.